An analysis of the 1974 Philippine Merchant Marine Academy Entrance Examination - Navarro, Patrocinio Ll. 1920- (1977)
This study analyzed the 1974 Philippine Merchant Marine Academy Entrance examination. The main objective of the study was to determine whether the PMMA entrance examination has the essential characteristics of a satisfactory measuring instrument in the admission of students in the Academy. A pool of experts was consulted to get the content validity of the test. As a basis for estimating the reliability of the test, the split-half method was employed and the Spearman-Brown Formula was applied. Findings of the study revealed that the present PMMA entrance examination needs not only refinement and modification but replacement.
Includes tables
Mimeographed
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Philippine Merchant Marine Academy; Universities and colleges -- Examinations. -- Philippines